2017
DOI: 10.1073/pnas.1705527114
|View full text |Cite
|
Sign up to set email alerts
|

Shelterin components mediate genome reorganization in response to replication stress

Abstract: The dynamic nature of genome organization impacts critical nuclear functions including the regulation of gene expression, replication, and DNA damage repair. Despite significant progress, the mechanisms responsible for reorganization of the genome in response to cellular stress, such as aberrant DNA replication, are poorly understood. Here, we show that fission yeast cells carrying a mutation in the DNA-binding protein Sap1 show defects in DNA replication progression and genome stability and display extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…SHREC directly interacts with the shelterin component Ccq1, linking Taz1, RITS, and HP1-containing silencing complexes. These analyses have now come full circle, as there is accumulating evidence for the role of shelterin components Taz1 and Ccq1 in heterochromatin formation at late replicating origins that are sites for double-strand break formation during meiosis and genome organization in general [114, 115]. Data obtained from high resolution three-dimensional structured illumination fluorescence microscopy (3DSIM) suggested that the “condensed” heterochromatin at subtelomeres in S. pombe is less condensed than nearby “knobs” that were eliminated by ablation of H3K36me3 [116], a histone mark correlated with gene expression and enriched in the 3â€Č regions of genes but actually repressing transcription from cryptic promoters and controlling transcript elongation [117, 118].…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…SHREC directly interacts with the shelterin component Ccq1, linking Taz1, RITS, and HP1-containing silencing complexes. These analyses have now come full circle, as there is accumulating evidence for the role of shelterin components Taz1 and Ccq1 in heterochromatin formation at late replicating origins that are sites for double-strand break formation during meiosis and genome organization in general [114, 115]. Data obtained from high resolution three-dimensional structured illumination fluorescence microscopy (3DSIM) suggested that the “condensed” heterochromatin at subtelomeres in S. pombe is less condensed than nearby “knobs” that were eliminated by ablation of H3K36me3 [116], a histone mark correlated with gene expression and enriched in the 3â€Č regions of genes but actually repressing transcription from cryptic promoters and controlling transcript elongation [117, 118].…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…SHREC directly interacts with the shelterin component Ccq1, linking Taz1, RITS, and HP1containing silencing complexes. These analyses have now come full circle, as there is accumulating evidence for the role of shelterin components Taz1 and Ccq1 in heterochromatin formation at late replicating origins that are sites for double-strand break formation during meiosis and genome organization in general [114,115]. Data obtained from high resolution three-dimensional structured illumination fluorescence microscopy (3DSIM) suggested that the "condensed" heterochromatin at subtelomeres in S. pombe is less condensed than nearby "knobs" that were eliminated by ablation of H3K36me3 [116], a histone mark correlated with gene expression and enriched in the 3â€Č regions of genes but actually repressing transcription from cryptic promoters and controlling transcript elongation [117,118].…”
mentioning
confidence: 99%
“…During G1/S phase, telomeres are anchored to the nuclear membrane, and Taz1-dependent origins tethered around the telomeres are suppressed by PP1. detected in the mutant cells of a chromatin-associated protein Sap1 (Mizuguchi et al, 2017). This was probably due to a transient interaction between internal late origins and telomeres during G1/S phase.…”
Section: Discussionmentioning
confidence: 85%
“…It is possible that this type of TAD contributes to formation of facultative heterochromatin around Taz1‐dependent late origins, although deletion of heterochromatin protein HP1 only marginally affected replication‐timing control (Zofall et al , ). The actual topological association between the chromosome arm regions and telomeres was not detected in wild‐type cells, but was detected in the mutant cells of a chromatin‐associated protein Sap1 (Mizuguchi et al , ). This was probably due to a transient interaction between internal late origins and telomeres during G1/S phase.…”
Section: Discussionmentioning
confidence: 99%